Depression and Obsessive-Compulsive Disorders Amid the COVID-19 Pandemic in Saudi Arabia - AlHusseini, Noara; Sajid, Muhammad; Altayeb, Afaf; Alyousof, Shahd; Alsheikh, Haifa; Alqahtani, Abdulrahman; Alsomali, Afrah (Curēus (Palo Alto, CA), 2021)
Coronavirus disease 2019 (COVID-19) is a global pandemic with significant morbidity and mortality. The Saudi government adopted mandatory home quarantine and curfew hours for all residents, excluding essential service workers. During the lockdown, the public's fear of infection can adversely impact mental health, causing psychological distress. The objective of this research is to assess frequency of depression and obsessive-compulsive disorder (OCD) among the general population during COVID-19 pandemic in Saudi Arabia. This was a cross-sectional study using the Patient Health Questionnaire (PHQ-9) and Obsessive-Compulsive Inventory-Revised assessment test (OCI-R) in Arabic and English languages distributed via social media platforms. Chi-square test was used with significance determined at p<0.005. We received a total of 2187 responses. Our results showed that being female, single, and unemployed had a higher frequency of suffering from depression whereas higher income levels and higher education was associated with less depression frequency. Increasing age, males, married individuals, higher income groups, higher levels of education and employed individuals were more likely to have OCD during COVID-19 pandemic.  Conclusion: The COVID-19 pandemic period is associated with significant mental health risks among the Saudi population. The results can provide further scientific support to better understand the impact of quarantine on psychological distress and mental health during emergency and disaster situations.